Plant Availability of Magnesium in Typical Tea Plantation Soils - Zhang, Qunfeng; Tang, Dandan; Yang, Xiangde; Geng, Saipan; He, Ying; Chen, Yupei; Yi, Xiaoyun; Ni, Kang; Liu, Meiya; Ruan, Jianyun (Frontiers in Plant Science, 2021)
Background and aims: Magnesium (Mg) plays important roles in improving the yield and quality of tea. However, Mg deficiency frequently occurs in acidic tea plantation soil. Methods: Tea plants were pot-cultivated in 12 typical tea plantations soils amended with and without Mg fertilizer. Exchangeable Mg (Ex-Mg) concentration in soils were quantitatively extracted using four extraction solutions (Mehlich-3, BaCl2, CaCl2 and NH4OAC). Plant availability of Mg was evaluated by Mg uptake and use efficiency, as well as its association with quality-components in tea plants. Results: Ex-Mg in soils were extracted most efficiently by Mehlich-3, while Mg concentrations in tea plant tissue higher correlated with Ex-Mg extracted by CaCl2 than other extraction solutions. Mg fertilizer use efficiency in tea plant varied from 6.08% to 29.56 %, and Mg fertilization significantly improve green tea quality by decreasing the ratio of total polyphenol to amino acid in tea leaves (24-60%). Moreover, the effect of Mg application on tea quality improvement and the use efficiency of Mg fertilizer both negatively correlated with total Mg concentration (r = -0.94 and -0.63, respectively) and nitrogen (N) level (r = -0.61 and -0.51, respectively) in soils prior to tea plant cultivation. Conclusions: CaCl2 could be recommended for plant-available Mg extraction in tea plantation soil, and Mg fertilizer use efficiency could be affected and predicted by total N and Mg status in soils prior to tea plant cultivation, providing a potential theoretical for guidance of Mg fertilization for tea yield and quality improvement in tea plantation management.